Reactive arthritis following treatment with intravesical Bacillus Calmette-Guerin for papillary carcinoma of bladder. Issue 4 (13th April 2022) - Singh, Yogesh Preet; Roy, Debaditya; Jois, Bhargavi; Shetti, Mohit
Abstract : A man in his 60s developed reactive arthritis following treatment with intravesical Bacillus Calmette-Guerin (iBCG) for papillary carcinoma of bladder. Evaluation revealed leucocytosis and raised inflammatory markers. HLA B27 was positive. Based on the temporal relationship, it was attributed to BCG-related reactive arthritis. iBCG was stopped. Treatment with non-steroidal anti-inflammatory drugs (NSAIDS) and glucocorticoids were ineffective. Prolonged course of disease-modifying antirheumatic drugs (DMARDS) was required which aided in alleviation of symptoms and sustained remission. Intravesical BCG therapy is a treatment for bladder cancer. It is rarely associated with reactive arthritis, which responds to discontinuation of iBCG and treatment with NSAIDS and/or short-term glucocorticoids. iBCG-related reactive arthritis commonly has an acute/subacute course. Chronic arthritis as observed in our case requiring prolonged treatment with DMARDS is rare.